Dyke Davidoff Masson Syndrome A Case Report - Taher, Md. Abu; Ahma, Fattah; Pasha, Md. Anwar; Sharif, Md. Mofazzal; Ul Alam, Md. Mohit; Rahman, Nayeema; Rahman, Md. Towhidur (BIRDEM Medical Journal, 2013)
A 10 year old male child reported to paediatric neurology OPD of BIRDEM General Hospital with the complaints of weakness of left side of body, seizure and facial asymmetry for 2 years. He was on regular anti convulsive therapy and failed to control seizure. General examination revealed no significant abnormality neither delayed mile stones of development happened. Neurological examination revealed left sided spastic hemiparesis, brisk tendon reflexes and extensor planter on left side. With detailed history and examination he was diagnosed as a case of infantile seizure and undergone CT scan of brain followed by MRI scan. Both the reports revealed severe atrophy of right cerebral hemisphere, thinning of cortical gyri, widening of sulci and dilatation of right lateral ventricle with ipsilateral midline shift and was concluded as hemiatrophy of right cerebral hemisphere with suspicion of Dyke Davidoff Masson Syndrome (DDMS), Hemimegalencephaly and Sturge-Weber syndrome. Dyke-Davidoff-Masson syndrome (DDMS) is a rare condition characterized by asymmetric cerebral hemispheric growth with unilateral atrophy, ipsilateral compensatory osseous hypertrophy, hyperpneumatization of the paranasal sinuses and mastoid cells, and contralateral paresis. Varying degrees of hemiparesis, hemiplegia, seizures, mental retardation, and facial asymmetry can be associated with DDMS. Considering clinical history and imaging findings, final Diagnosis was Dyke Davidoff Masson Syndrome. Birdem Med J 2013; 3(2): 196-109 DOI: http://dx.doi.org/10.3329/birdem.v3i2.17215